YY1/LncRNA GAS5 complex aggravates cerebral ischemia/reperfusion injury through enhancing neuronal glycolysis. (1st November 2019) - Zhang, Xin-Chun; Gu, Ai-Ping; Zheng, Chun-Ye; Li, Ying-Bin; Liang, Hong-Feng; Wang, Hua-Jun; Tang, Xia-Lin; Bai, Xiao-Xin; Cai, Jun
Abstract: Yin-Yang 1 (YY1) has been identified as playing critical roles in multiple diseases. However, little is known regarding its roles and mechanisms in cerebral ischemia/reperfusion (I/R) injury. This study is aimed to explore the roles of YY1 in regulating neuronal apoptosis in cerebral I/R injury and its underlying mechanisms. Primary mouse cerebral cortical neurons were isolated and subjected to OGD/R to mimic cerebral I/R injury in vitro . The roles of YY1 on OGD/R-induced neuronal injury were investigated by performing western blotting, quantitative real-time polymerase chain reaction, TUNEL, RNA-binding protein immunoprecipitation, chromatin immunoprecipitation, chromatin isolation by RNA purification assay, glucose uptake assay, lactate production assay, and extracellular acidification rate assay. YY1-binding long non-coding RNAs (LncRNAs) in neurons subjected to OGD/R were identified by RIP and RNA sequencing. The roles of YY1 on cerebral I/R in vivo were detected by assessing neuronbehaviour, infarct size, and neuronal apoptosis. We found that YY1 expression is downregulated, and LncRNA GAS5 is upregulated in neurons subjected to OGD/R. OGD/R treatment promotes YY1 interacting with GAS5 in neurons, and YY1 negatively regulates GAS5 expression by binding to GAS5 promoter to repress its transcription. Besides, YY1 and GAS5 bind to the same region of PFKFB3 promoter to promote PFKFB3 expression and strengthen neuronal glycolysis, resulting in aggravating OGD/R-induced neuronal apoptosis. Knockdown of YY1 or GAS5 protects against I/R-induced ischemic brain damage and improves overall neurological functions in vivo. Overall, YY1 interacts with LncRNA GAS5 to promote PFKFB3 transcription to enhance neuronal glycolysis, resulting in aggravating cerebral I/R injury. Highlights: YY1 participates in OGD/R-induced neuronal apoptosis. OGD/R treatment promotes YY1 interacting with LncRNA-growth arrest specific 5 (GAS5) in neurons. YY1/GAS5 complex promotes OGD/R-induced neuronal apoptosis by upregulating glycolysis. YY1/GAS5 complex promotes neuronal glycolysis by upregulating PFKFB3 gene.